Identifikasi Potensi dan Strategi Pengembangan Ekowisata di Kabupaten Aceh Tamiang (Studi Kasus : Ekowisata Kuala Paret) - Safuridar; Putri Andiny; Dian Aswita; Asnariza; Umi Umaya Harahap (Kodepena Indonesia, 2023)
This study aims to identify the potential and strategies for developing ecotourism in Aceh Tamiang District. The analytical method used is SWOT analysis (Strengths, Weaknesses, Opportunities and Threats). The results of the analysis show that the Kuala Paret tourist area has strengths and opportunities that can be developed as an aggressive strategy; The strategy for developing Kuala Paret ecotourism in Kaloy Village, Tamiang Hulu District, Aceh Tamiang Regency is the need for publication about the area on social media, spatial planning for tourist sites, training on businesses related to tourism for local human resources, the need for more financing to provide supporting facilities and infrastructure.